Satisfacción laboral y desempeño laboral de los colaboradores de la unidad de gestión educativa de local-Nauta periodo julio 2023 - Lopez Vega, Sergio Alberto (2024)
The objective of the research is to establish the relationship between Job Satisfaction and Job Performance of the collaborators of the Local Educational Management Unit -Nauta, period July 2023; For this purpose, a non experimental, correlational and cross-sectional research design was used. The hypothesis proposed was that there is a significant positive relationship between Job Satisfaction and Job Performance of the collaborators of the Local Educational Management Unit -Nauta, period July 2023, the population was made up of 31 administrative collaborators and the data was collected through a structured questionnaire and the research concludes that with a Pearson correlation coefficient of 0.838 it is inferred that there is a positive connection between these two variables, therefore, the higher the level of job satisfaction there will be better job performance.